Effect of aspirin and other non-steroidal anti-inflammatory drugs on prostate cancer incidence and mortality: a systematic review - Abdulaziz sowalah almotairi, Rashed Shakeer Alzahrani, Abdulhadi zaid almalki, Abdullah grosh Almalki, Fahad Ali Althagafi, Ranya Abdullah bajuo, Aiman Hussein Alzahrani, Hasan Mousa Alzahrani (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
Prostate cancer constitutes fifteen percent of all cancers diagnosed in males, it ranks fifth in terms of cancer-related fatalities; and it contributes to 6.6% of all male mortality. Aim and objectives: To assess the impact of non-steroidal anti-inflammatory drugs (NSAIDs), including aspirin, on the incidence and mortality of prostate cancer. Patients and methods: This systematic review was performed in April 2021 and chose the related study from PubMed, Web of Science databases, Embase with the following keywords: (“prostate cancer” or “prostate tumor”), (“aspirin” or “acetylsalicylic acid”) ‘anti-inflammatory agents’, ‘NSAID’, and ‘NSAID*. Results: The current study documented that Regular current aspirin use was found to be correlated with a reduced risk of fatal PC in all participants. The correlation between current post-diagnostic use and increased survival after diagnosis is consistent with the possibility that aspirin inhibits the development of PC. The use of aspirin was not correlated with the incidence of prostate cancer. In contrast, the use of aspirin was inversely correlated with mortality from prostate cancer. Consistent among both white and black men, this association appeared to be limited to men who took aspirin every day or for the prevention of cardiovascular disease. The use of NA-NSAIDs did not correlate with these endpoints. Conclusion: Potential benefits of aspirin use, as long-term use, include a decreased incidence &mortality rate associated with prostate cancer. Advanced prostate cancer exhibited a significantly increased inverse correlation in comparison to total prostate cancer.